Past Shift Work and Incident Coronary Heart Disease in Retired Workers: A Prospective Cohort Study. Issue 9 (17th March 2021) - Li, Wending; Yu, Kuai; Jia, Ningning; Xu, Xuedan; Yuan, Yu; Peng, Rong; Niu, Rundong; You, Xiaomin; Yang, Handong; Qiu, Gaokun; Guo, Huan; He, Meian; et al.
Abstract: Present shift work has been associated with coronary heart disease (CHD) among employed workers, but it remains unclear whether shift work performed in the past is still associated with CHD in retired workers. We recruited 21, 802 retired workers in Shiyan, China, in 2008–2010 and 2013 and followed them for CHD events occurring up to December 31, 2018. Retired workers with longer durations of past shift work (rounded to 0.25 years) had higher CHD risks (for those with ≤5.00, 5.25–10.00, 10.50–20.00, and >20.00 years of past shift work, hazard ratios were 1.05 (95% confidence interval (CI): 0.94, 1.16), 1.08 (95% CI: 0.94, 1.25), 1.23 (95% CI: 1.07, 1.42), and 1.28 (95% CI: 1.08, 1.51), respectively). The association was substantially higher among service or sales workers than among manufacturing or manual-labor workers (for every 5-year increase in past shift work, hazard ratio = 1.11 (95% CI: 1.05, 1.16) vs. hazard ratio = 1.02 (95% CI: 0.98, 1.06)). Moreover, the risk was lower among those who were physically active than among their inactive counterparts ( P for interaction = 0.019). Longer duration of past shift work was associated with higher risk of incident CHD among these retired workers, especially those from the service or sales sectors. Physical exercise might be beneficial in reducing the excess risk.